ANALYSIS OF FACTORS AFFECTING INVESTMENT IN BALI PROVINCE 2019 – 2022 - Aziz Adi Permana; Siti Fatimah Nurhayati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Investment is the act or process of allocating a certain amount of funds in the hope of obtaining future profits. This study aims to analyse the influence of the human development index (HDI), gross regional domestic product (GRDP) per capita, labour force (AK), and district/city minimum wage (UMK) on investment in the province of Bali from 2019 to 2022. This study utilises secondary data in the form of panel data, specifically incorporating cross-sectional data from 9 districts / cities in Bali Province and time series data covering the observation range 2019 - 2022. The data analysis technique employed in this study is panel data regression using the Fixed Effect Model (FEM) as the chosen model. The findings indicated a negative correlation between gross regional domestic product (GRDP) per capita and investment. Concurrently, the human development index (HDI), labour force (AK), and district/ city minimum wage (UMK) have no effect on investment in Bali province in 2019-2022. Keywords: Investment, HDI, GRDP per capita, Labor Force, Minimum Wage